(untitled) (African Journal of Biomedical Research, 2021)
This study evaluated the effects of Nigerian Bee Propolis extract on Methicillin Resistance Staphylococcus Aureus (MRSA) infected skin wounds of albino rats. Two full thickness circular wounds were created each on the dorsum of eighteen (18) healthy adult male albino rats with mean body weight of 126±7.09g. Each wound was contaminated with 108 colony forming unit of MRSA. The rats were then randomized into three (3) treatment groups (n=6) with topical application of Propolis extract (PE Group), Silver sulphadiazine (SS Group) and untreated Control (UT Group). Gross wound healing indices (exudation, edema, hyperemia, wound contraction), histopathologic (granulation, angiogenesis, fibroplasia, epithelialization) and immunologic healing indices were evaluated using standard methods. Bacteria clearance was through culture and quantification. The wound surface exudation and edge edema and hyperemia were prominent in all the groups from day 0 to 6 but persisted in the untreated group till day 12. Wound contraction was gradual in all the groups from day 0-18, it was higher between days 0 and 3 in the PE and SS than the UT group (P<0.05). Complete wound closure occurred on SS (day 15), and PE (day 16). The histopathological changes observed showed neutrophils regressed on day 6 to 18 in all groups and was faster in PE and SS groups (P<0.05). Platelets reduction was ` gradual from days 3 to 18 in all groups and was absent from days 6 to 18 in the PE group. Nigerian Bee propolis has a profound bacteria clearance and healing effect on wound infected with methicillin resistant staphylococcus aureus (MRSA) comparable to silver sulphadiazine and therefore recommended for infected wound treatment